Air lime mortars with vegetable fat addition: characteristics and research needs - Shasavandi, Arman (2010)
Although history reveals that air lime mortars with added vegetable fat (ALVF) were used very often in the past, little knowledge about them survives to modern times. Little is known about the influence of fat addition on the mortars’ durability, and some details about their manufacture and application are completely unknown. Even less is understood about the mechanisms that explain the behavior of ALVF-based mortars that also contain pozzolans. This paper reviews current knowledge about the characteristics of ALVF-based mortars in order to highlight questions that must be addressed in future research.